Ukraine and Kazakhstan as Two Former Soviet Republics in The Light of Hofstede’s Dimensions and Gray’s Model of Accounting Subculture - Malgorzata CZERNY (Communications of International Proceedings, 2024)
The study aims to compare the cultural dimensions of two former Soviet Union countries, Ukraine and Kazakhstan, using G. Hofstede’s cultural dimensions and S.J. Gray’s subculture of accounting framework. This comparison seeks to identify potential features of their accounting systems influenced by their cultural backgrounds. The literature lacks comprehensive studies on how the Soviet Union’s legacy impacts the accounting systems of its former member states, making this research crucial. This paper is filling the existing cognitive gap also because former Asian Soviet republics (like Kazakhstan) and their accounting systems are rarely studied in a cultural context. The methodology involves a critical and comparative literature analysis, but primarily abduction, which serves as the basis for interpretive reconstruction of causes and intentions, as well as the inventive construction of theories. This approach led to the preliminary characterization of Ukrainian and Kazakhstani accounting subcultures, highlighting a strong inclination towards conservatism, discretion in disclosures, statutory control, and unified solutions. The findings suggest that despite geographical, ethnic, religious, and historical differences, the prolonged membership in the Soviet Union significantly influenced the cultural and social values of these countries. According to Hofstede’s theory of culture as a “mind-programmer,” this influence may have led to the development of similar economic and accounting systems. This study contributes to the ongoing discussion on the impact of culture on accounting systems and provides a foundation for further research.